Efektifitas Penyelenggaraan Pelayanan Perizinan IMB Studi Kasus di Badan Pelayanan Perizinan Terpadu Satu Pintu Kota Samarinda - Andella Nur Handayani (Universitas 17 Agustus 1945 Samarinda, 2021)
Samarinda City itself based on The Minister of Home Affairs Regulation No. 24 of 2006 concerning guidelines for the implementation of One-Door Integrated Services (PTSP) and the Permendagri National Guidelines launched in May 2007 established a One-Door Integrated Licensing Service Agency to implement PTSP. Related to that, researchers want to describe the effectiveness of IMB licensing services that focus on achieving simple, fast, precise, and comfortable service goals for the community. And, to find out what factors are obstacles in the implementation of IMB licensing services in BPPTSP Samarinda City. Data collection is carried out with literature research techniques and field research consisting of observations, interviews, and documentation. Nara source is determined through purposive sampling technique, namely BPPTSP employees / staff and using incidental sampling, namely the community of service recipients at the One Door Integrated Licensing Service Agency in Samarinda City. The collected data is analyzed through three stages: data reduction, presentation of data and withdrawal of conclusions or verification. The results of the study describe the effectiveness of the implementation of IMB licensing services in the One Door Integrated Licensing Service Agency of Samarinda City judging from the achievement of simple, easy, and convenient service objectives seen from indicators of service procedures and comfort of the service environment has been achieved while for the purpose of fast and precise service has not been achieved optimally. Based on the achievement of the service objectives that have been successfully achieved, the IMB licensing service has been carried out effectively because the indicator of the goals achieved is more than has not been achieved. As for the inhibiting factors there are: lack of facilities and infrastructure, lack of professional employees.Kota Samarinda sendiri berdasarkan Peraturan Menteri Dalam Negeri Nomor 24 Tahun 2006 mengenai pedoman penyelenggaraan Pelayanan Terpadu Satu Pintu (PTSP) serta Panduan Nasional Permendagri tersebut yang diluncurkan bulan mei 2007 membentuk Badan Pelayanan Perizinan Terpadu Satu Pintu untuk melaksanakan PTSP. Berkaitan dengan hal itu peneliti ingin mendeskripsikan mengenai efektivitas penyelenggraan pelayanan perizinan IMB yang memfokuskan pada tercapainya tujuan pelayanan yang sederhana, cepat, tepat dan nyaman bagi masyarakat. Dan juga untuk mengetahui faktor-faktor apa saja yang menjadi penghambat dalam penyelenggaraan pelayanan perizinan IMB di BPPTSP Kota Samarinda. Pengumpulan data dilakukan dengan teknik penelitian kepustakaan dan penelitian lapangan yang terdiri dari observasi, wawancara dan dokumentasi. Nara sumber ditentukan melalui teknik sampling purposive yaitu pegawai/staf BPPTSP dan menggunakan sampling incidental yaitu masyarakat penerima pelayanan di Badan Pelayanan Perizinan Terpadu Satu Pintu Kota Samarinda. Data-data yang dikumpulkan dianalisis melalui tiga tahap yaitu : reduksi data, penyajian data dan penarikan kesimpulan atau verifikasi. Hasil penelitian mendeskripsikan efektivitas penyelenggaraan pelayanan perizinan IMB di Badan Pelayanan Perizinan Terpadu Satu Pintu Kota Samarinda dilihat dari tercapainya tujuan pelayanan yang sederhana, mudah dan nyaman yang dilihat dari indikator prosedur pelayanan dan kenyamanan lingkungan pelayanan telah tercapai sedangkan untuk tujuan pelayanan yang cepat dan tepat belum tercapai secara optimal. Berdasarkan tercapainya tujuan pelayanan yang berhasil tercapai maka pelayanan perizinan IMB telah terselenggara dengan efektif karena indicator tujuan yang tercapai lebih banyak dibandingkan yang belum tercapai. Sedangkan untuk faktor-faktor penghambat terdapat : kurangnya sarana dan prasarana, kurangnya pegawai yang professional.